2019
DOI: 10.3390/ijms20225574
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Computational Approaches Towards Identifying Malarial Allosteric Modulators: A Case Study of Plasmodium falciparum Hsp70s

Abstract: Combating malaria is almost a never-ending battle, as Plasmodium parasites develop resistance to the drugs used against them, as observed recently in artemisinin-based combination therapies. The main concern now is if the resistant parasite strains spread from Southeast Asia to Africa, the continent hosting most malaria cases. To prevent catastrophic results, we need to find non-conventional approaches. Allosteric drug targeting sites and modulators might be a new hope for malarial treatments. Heat shock prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 94 publications
2
20
0
Order By: Relevance
“…Intriguingly, some of the residues possessing high BC values, 10-14, 57-63, 159-162, and 180-184, form part of the positively charged groove at the back of the active site responsible for critical interactions (with the negatively charged junction region helix 285-294) necessary for Pf DHFR-TS protein folding and function [21,34,35]. These findings are in agreement with previous studies which found high centrality residues around active site and linker interphases of protein domains [23,30,33]. Using WT holoenzyme as reference, twenty-four key communication residues were identified: 10, 13, 15, 16, 18, 21, 41, 55, 59, 63, 101, 103, 105, 109, 159, 162, 163, 165, 167, 170, 180, 181, 185, and 196.…”
Section: Dynamic Residue Network Analysissupporting
confidence: 92%
See 3 more Smart Citations
“…Intriguingly, some of the residues possessing high BC values, 10-14, 57-63, 159-162, and 180-184, form part of the positively charged groove at the back of the active site responsible for critical interactions (with the negatively charged junction region helix 285-294) necessary for Pf DHFR-TS protein folding and function [21,34,35]. These findings are in agreement with previous studies which found high centrality residues around active site and linker interphases of protein domains [23,30,33]. Using WT holoenzyme as reference, twenty-four key communication residues were identified: 10, 13, 15, 16, 18, 21, 41, 55, 59, 63, 101, 103, 105, 109, 159, 162, 163, 165, 167, 170, 180, 181, 185, and 196.…”
Section: Dynamic Residue Network Analysissupporting
confidence: 92%
“…Overall, regions showing significantly high BC values were located within or close to substrate/ligand-binding sites (shaded grey in Figure 7). These results recapitulate previous findings reporting that active sites of proteins possess high and low average BC and average L values, respectively [23,30,33].…”
Section: Dynamic Residue Network Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…Another important incentive for the development of allosteric drugs is that, while traditional orthosteric drugs usually inhibit protein activity, allosteric modulators may not only inhibit but also increase protein activity (allosteric activators) [29]. In the last decade, drug discovery has been shifting its focus toward targeting allosteric sites in order to improve compound selectivity [28][29][30][31][32][33]. Allosteric drugs also feature distinct physicochemical properties, adding further freedom for discovery of novel active compounds, and can often be combined with orthosteric drugs into synergistic drug cocktails to modulate and improve enzyme activities, specificity, and pharmacological profiles.…”
Section: Introductionmentioning
confidence: 99%